(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2026)
This article examines the intricate relationship between oral tradition and the construction of cultural identity among Vietnam’s ethnic minorities. As a multi-ethnic country, Vietnam possesses a rich treasury of folk narratives that serve not only as artistic heritage but also as living cultural archives. These narratives safeguard values, social structures and cosmological views transmitted across generations. Drawing on an interdisciplinary framework that combines folklore studies, cultural anthropology and Walter J. Ong’s perspectives on orality and literacy, the study argues that folk narratives represent a dynamic space where cultural identity is performed, retold, revised and continually re-created. The analysis highlights typical examples from the Ede epic Dam San, the Tay-Nung process of “localising” narrative poems and the Southeast Asian motif of the “persecuted orphan girl”. These cases demonstrate how oral storytelling functions as a strategy for minority communities to assert distinctive cultural identities amidst the pressures of globalisation and the transition toward literacy. The findings underscore the enduring vitality of oral traditions as cultural memory and their relevance to contemporary discussions on identity, education and cultural sustainability.